LZTR1 expression as a novel predictive biomarker for early recurrence of hepatocellular carcinoma - Xi Yu; Shuqi Mao; Yuying Shan; Kedan Cen; Caide Lu; Yi Huang (European Journal of Medical Research)
Abstract Effective biomarkers for predicting early recurrence (ER) (within one-year post-surgery) of hepatocellular carcinoma (HCC) are lacking. LZTR1, a known tumor suppressor, plays a role in HCC development. This study investigated the correlation between LZTR1 expression and ER of HCC and its effects on HCC cells. Clinical data of 101 HCC patients were collected to evaluate tumor prognostic factors. ROC curve analysis was used to evaluate the predictive ability of LZTR1 in HCC. Huh7 cells and SK-Hep-1 cells were used for cell experiments to observe the effects of knocking out LZTR1 on tumor cell proliferation and metastasis. Cox analysis showed that alpha-fetoprotein (P = 0.010), LZTR1 (P = 0.014), tumor number (P = 0.032), and portal vein tumor thrombus (P = 0.001) as independent factors associated with ER of HCC. The one-year recurrence-free rate of HCC patients with high LZTR1 expression (≥ 1.7) was 73.2%, while that of patients with low LZTR1 expression (< 1.7) was 41.4% (P = 0.009). ROC curve analysis showed that LZTR1 expression had early predictive value for HCC (AUC = 77.9%). In vitro LZTR1 knockdown promoted HCC cell proliferation and metastasis. Mechanistically, LZTR1 downregulation increased RAS protein expression, leading to MAPK pathway activation and enhanced epithelial-mesenchymal transition. In conclusions, this study revealed that LZTR1 acts as a tumor suppressor in the pathological process of HCC. LZTR1 expression might be used as an effective predictive marker for ER of HCC.